Antioxidant and Anti-Inflammatory Phytochemicals for the Treatment of Inflammatory Bowel Disease: A Systematic Review - George Pantalos; Natalia Vaou; Smaragda Papachristidou; Elisavet Stavropoulou; Christina Tsigalou; Chrysa Voidarou; Eugenia Bezirtzoglou (Applied Sciences, 2024)
Inflammatory bowel disease (IBD) remains a burden for patients with increasing prevalence in industrialized countries. Phytochemicals are non-nutrient plant derived bioactive substances with antioxidant and anti-inflammatory effects that may prove beneficial to IBD patients. This review aims to overview current evidence on the application and impact of isolated phytochemicals or phytochemicals contained in plant extracts and essential oils on patients suffering from IBD. A systematic literature search was conducted for studies relating to the use of phytochemicals for the treatment of IBD. Ultimately, 37 human clinical trials and 3 systematic reviews providing human IBD patient data relevant to phytochemicals as therapeutic agents were included. Phytochemicals in the form of curcumin, Plantago ovata seeds, polyphenon E, silymarin, resveratrol supplements or an herbal preparation of myrrh, chamomile and coffee charcoal have evidence from human clinical trials supporting their safety and beneficial effects. Cannabinoids improve quality of life but not IBD outcomes. The addition of probiotics like B. longum to fructo-oligosaccharides promote healthy composition of the gut microbiome. Phytochemicals like mastiha, anthocyanins, berberine, tormentil, T2, ecabet sodium and Pycnogenol need more well-designed trials. Systematic research on phytochemicals can lead to the discovery of useful therapeutics. These secondary metabolites can be incorporated in current IBD treatment strategies to limit side effects, promote mucosal healing and provide higher quality of life to patients.